Technical Guidelines for the Safe Movement of Cacao Germplasm. Revised from the FAO/IPGRI Technical Guidelines No. 20 (Fifth Update 2024) - End, Michelle J.; Daymond, Andrew J.; Hadley, Paul (Bioversity International, 2024)
The CacaoNet Technical Guidelines for the Safe Movement of Cacao Germplasm provide updated information on the precautions and quarantine measures that can be taken to minimise the risk of spread of pests and diseases when cacao genetic resources are being moved for research, crop improvement, plant breeding, exploration or conservation. These Guidelines are based on those last published by FAO/IPGRI in 1999 but have been revised and expanded by a group of experts set up within CacaoNet (the Global Cacao Genetic Resources Network coordinated by Bioversity International), to take account of new knowledge of the pests and diseases, including their current distribution, and advances in detection techniques. These CacaoNet Guidelines were first published on-line in 2012 but have been revised in 2014, 2017, 2021 and now 2024 to take account of new information received. The document includes general advice regarding safe procedures to use when moving cacao germplasm, whether as seed, vegetative and tissue cultured materials, and summarised information on the geographical spread and risks posed by significant pests and diseases of cacao. In addition, experts have contributed sections giving detailed information on the following: Virus diseases (Cacao necrosis virus, Cacao swollen shoot virus (CSSV) and other Badna viruses, Cacao Yellow mosaic virus), Fungal diseases (Witches’ broom disease, Moniliophthora pod rot, Phytophthora pod rot, Vascular streak die-back, Verticillium wilt, Ceratocystis wilt, Rosellinia root rot), Insect pests (Cocoa pod borer, mirids/capsids, mosquito bug, other insect pests) and nematodes. Each section contains information on physical symptoms, geographical distribution, biology of the pest or disease and recommended quarantine measures. The publication of these Guidelines has been supported by financial and in-kind contributions from Bioversity International, the CGIAR Research Programme on Forests, Trees and Agroforestry, the Cocoa Research Association Ltd., UK (CRA Ltd., a UK-based organization managing scientific cocoa research on behalf of Mars Mondelēz International and the London Cocoa Trade (ICE Futures Europe) and the University of Reading. CacaoNet has received additional financial support from Mars, the U.S. Department of Agriculture, Agricultural Research Service (USDA/ARS) and the World Cocoa Foundation (WCF).